Framing terrorism: the news media, the government and the public - Norris, Pippa (Routledge, 2003)
Framing terrorism / Pippa Norris, Montague Kern and Marion Just -- Terrorism, censorship and the 1st Amendment : in search of policy guidelines / Doris A. Graber -- Clausewitz in the age of CNN : rethinking the military-media relationship / Robin Brown -- Framing the Palestinian-Israeli conflict / Tamar Liebes and Anat First -- Paramilitaries and the press in Northern Ireland / Tim Cooke -- Framing the US Embassy bombings and September 11 attacks in African and US newspapers / Todd M. Schaefer -- CNN and al Jazeera's media coverage of America's war in Afghanistan / Amy E. Jasperson and Mansour O. El-Kikhia -- Framing Muslim-Americans before and after 9/11 / Brigette L. Nacos and Oscar Torres-Reyna -- Framing world opinion in the elite press / Frank Louis Rusciano -- Explaining 9/11 / Michael W. Traugott and Ted Brader -- Public opinion among Muslims and the West / Pippa Norris and Ronald Inglehart -- Rallies all around : the dynamics of system support / Paul Brewer, Sean Aday and Kimberly Gross -- Fear and terrorism : psychological reactions to 9/11 / Leonie Huddy ... [et al.] -- The lessons of framing terrorism / Montague Kern, Marion Just and Pippa Norris